Dyslexia in Reading Arabic Script among Arabs - Maulana, Muhammad Rifqi (Jurnal Al-Maqoyis, 2025)
This study examines the barriers to learning to read Arabic script among female students of Arab descent who have dyslexia at MI Al-Irsyad Al-Islamiyyah Banjarmasin. The main focus of the study is to identify the type of dyslexia experienced and to explore effective alternative methods for overcoming these difficulties. Using a descriptive qualitative approach with case studies, data was collected through observation, interviews, and documentation, which was then analyzed using the Miles and Huberman model. The results of the study indicate that the students experience visual (diseidetis) and verbal (linguistic) dyslexia, which causes an inability to consistently recognize Arabic letters and accurately associate sounds with letters. These challenges led to a reliance on Latin letters and significant difficulties in mastering the Arabic alphabet. Multisensory learning methods, the use of interactive media such as flashcards and digital applications, and the “reading without spelling” approach were found to be effective in reducing learning difficulties. Active parental involvement and psychological support also played crucial roles in the learning process. This study underscores the need for inclusive, personalized, and adaptive learning strategies for children with dyslexia, particularly in the context of Arabic script learning. These findings contribute significantly to the development of intervention models and the improvement of Arabic language education quality for children with special needs.